The Effect of Workload and Work Stress on Turnover Intention Among Production Employees - Maretha Pingkan Ardana; Hesty Prima Rini (PT Larva Wijaya Penerbit, 2025)
Human resources are crucial to a company's success and smooth operation. In order to retain quality employees, create a conducive work environment, and improve employee welfare, companies must implement effective resource management strategies that reduce turnover intentions. This study aims to analyze the effect of workload and work stress on turnover intentions at PT. XYZ. A quantitative approach involving 63 production employees was used, obtained through saturated sampling techniques. Data were collected by distributing questionnaires and analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS software. The results reveal that workload has a positive and significant effect on turnover intention. Additionally, work stress positively and significantly affects turnover intention. These findings suggest that the greater the workload, the greater the likelihood that employees will leave the company. Similarly, work stress, or pressure due to role demands, is the dominant factor in experiencing work stress and increasing turnover intention.